Innovative mixed-residential waterfront development proposals for sustainable livelihood in urban Kuantan, Malaysia - Azmin, Aida Kesuma; Azman, Tahirah Zahirah (UniversityPublications.net, 2014)
This paper primarily highlights an appraisal of an undergraduate architectural student’s work for a third year design studio project on a mixed-residential waterfront development, which aims to achieve sustainable livelihood for Kuantan’s urban community. Dwelling architecture demands good architects to respond holistically towards the local contexts, and people’s socio-cultural-economics activities. Kuantan’s waterfront principal issue is the deteriorating wetland eco-system. The environmental degradation of the existing tropical wetlands is caused by forest clearing and land reclamation activities. Since 1980s, Malaysia’s city centres have experienced exponential growth in the urban population - caused by rural-urban migration - due to the shift of national economic development from agricultural and mineral resources output, to industrial production. Hence, the demand for affordable housing has also increased exponentially. Housing needs are more demanding for the low-income groups. The rapid urbanization in Malaysia is currently estimated at 65%. The decline in the farming population phenomenon is synonymous with development. Whilst government’s strategy is to encourage the evolution of large farms and rural migration to higher value-added jobs, other economic sectors offer better prospects of reducing rural poverty. The decrease in younger population’s interest in agriculture is also a concern. The aged and less educated in the sector may not be ready to uphold the required initiative to develop value-added sustainable practices. In this light, the mixed-residential waterfront development scheme proposals offers to respond to these issues with the objectives: to provide “sustainable livelihood” so as to sustain the eco-system; initiate a well-balanced housing community, and stimulate innovative solutions for the community’s self-sustenance. The proposed mixed residential waterfront development scheme is envisioned to be the national reference for sustainable livelihood in Malaysia, and a medium for interaction to disseminate community awareness about individual and social responsibility towards sustaining the urban eco-system and its community. Keywords: Mix-use waterfront development, Sustainable livelihood, Urban housing design, Cultural meanings.